Harnessing low‐grade waste heat by operating a hybrid piezoelectric‐electromagnetic energy harvester combined with a thermomagnetic engine. (28th July 2020) - Zeeshan,; Ahmed, Rahate; Mehmood, Muhammad Uzair; Kim, Yeongmin; Lee, Jaeyoung; Chun, Wongee
Summary: This work deals with the development of a thermomagnetic engine driven by using a magnetocaloric material (gadolinium), coupled with both a disk‐shaped electromagnetic generator (EMG) and a flexible piezoelectric generator (PENG). The thermomagnetic engine generated the highest rotational speed with an average of 226 ± 1.76% rpm when the temperature differed by 45°C between the hot and cold water jets that operate the engine. At this rotational speed, the EMG and TENG deliver output powers of 8.4 mW (corresponding to the power per unit/volume of 81 W/m 3 ) at a loading resistance of 100 Ω and 74.4 nW (corresponding to the power per unit/volume of 7.2 mW/m 3 ) at a loading resistance of 20 kΩ, respectively. Moreover, the hybrid (EMG‐PENG) generator exhibited outstanding performance whose respective short circuit current and open circuit voltage was recorded to be3.6 mA and 7.5 V. It showed a combined power output of 7.8 ± 2.1% mW. The proposed energy harvester demonstrated its capability to charge a 1000 μF capacitor which can be used as an effective power source for diverse smart applications. It was found that the operation of the hybrid (EMG‐TENG) generator in line with the thermomagnetic engine holds great potential in harnessing low‐grade thermal energy with high added value as compared to common practices in its utilization. Abstract : The operation of the hybrid (EMG‐TENG) generator in line with the thermomagnetic engine holds great potential in harnessing low‐grade thermal energy with high added value as compared to common practices in its utilization. The thermomagnetic engine produced the highest average rotational speed of 226 ± 1.76% rpm when the temperature difference between the hot and cold water jets driving the engine reached 45°C delivering power output of 8.4 mW at a loading resistance of 100 Ω.